HELICOBACTER PYLORI DETECTION IN CHRONIC GASTRITIS: A COMPARISON OF STAINING METHODS - Ahmad, Fiaz; Jaffar, Rozina; Khan, Inamullah (Journal of Ayub Medical College Abbottabad, 2011)
Background: Helicobacter pylori is an important cause of chronic gastritis, gastric ulceration and gastric malignancies as gastric carcinoma and MALT lymphoma. Its definitive diagnosis is based on histopathology. Routine H & E stain is not very effective in its detection, immune-stains and fluorescent stains are costly. Need for simple cheap and sensitive stain has always been a topic of hot debate and extensive research. Method: paraffin embedded blocks of all adult patients diagnosed as chronic gastritis/gastric ulceration with no accompanying gastric pathology as hypertrophic gastropathys, and neoplasias were taken into study. Three sections of 4 micron were cut and stained with routine H & E, Giemsa, and Cresyl fast violet. Results: Total number of patients was 50. Out of these 37 (74%) were males and 13 (26%) were females. Mean age of the patients was 50.4 years. Thirty-four percent (34%) were positive in normal H & E stain, 68% were positive in Giemsa and 76% were positive in Cresyl fast violet. Conclusion: Cresyl fast violet is a good stain for diagnosis of H. pylori gastritis. Keywords: H pylori, chronic gastritis, H pylori staining methods